(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
The rapid expansion of the digital environment has significantly transformed the conditions of early childhood development, particularly affecting the emotional-volitional sphere of preschool children. This study examines the key features of emotional regulation, volitional control, motivation, and behavioral self-management of preschool-aged children within digitally mediated contexts. The research analyzes both the developmental opportunities and the potential risks associated with early exposure to digital technologies, including interactive media, educational applications, and virtual communication. Special attention is given to changes in emotional responsiveness, impulse control, attention regulation, and the formation of perseverance and self-control skills. The findings indicate that while appropriately designed digital resources can support emotional engagement and cognitive motivation, excessive or unregulated use may lead to emotional instability, reduced frustration tolerance, and weakened volitional regulation. The study emphasizes the importance of balanced digital interaction, adult mediation, and psychologically informed pedagogical strategies to foster healthy emotional-volitional development in preschool children within the digital environment.